Soil Ingestion Rate and Excess Lifetime Cancer Risk in First Nations’ People Exposed to Polycyclic Aromatic Hydrocarbons Near In-situ Bitumen Extraction in Cold Lake, Alberta - Irvine, Graham (Université d'Ottawa / University of Ottawa, 2013)
The inadvertent ingestion of contaminated soil is the dominant exposure route of non-volatile and semi-volatile contaminants such as polycyclic aromatic hydrocarbons (PAHs). Quantitative mass balance soil ingestion studies have been used to determine soil ingestion rates for use in human health risk assessments (HHRA) that can be used to predict the likelihood of adverse effects in individuals exposed to hazardous contaminants such as PAHs in contaminated soil. The Cold Lake region of Alberta is one of the three major oil sands regions of Alberta, and PAH concentrations in this oil sand region may be elevated in the atmosphere and the soil, resulting in increased exposures to PAHs. The area is home to Cold Lake First Nation who practice traditional activities and lifestyles that may put them in greater contact with soil than previous soil ingestion studies suggest. The primary objective of this research was to assess the soil ingestion rate in a group of First Nations subjects inhabiting the Cold lake region, and assess the carcinogenic risk posed by exposures to PAHs in air and soil. The study employed a quantitative mass balance tracer approach to estimate soil ingestion rates, and followed 9 subjects over a 13 day period. Soil and air samples were simultaneously collected to assess PAH contamination. The mean soil ingestion rate using Al and Si elemental tracers was 52 mg d-1, with a 90th percentile of 220 mg d-1, and a median soil ingestion rate of 37 mg d-1. These values are greater than the soil ingestion rates for HHRA recommended by Health Canada. The mean increase in excess lifetime cancer risk posed by inadvertent ingestion of soil to a First Nations’ individuals following traditional activities was 0.02 cases per 100,000 people with a 95% risk level of 0.067 cases per 100,000 people. Exposure to PAHs through inhalation posed a maximum lifetime cancer risk below 0.1 cases per 100,000, people. Thus, this study found no appreciable increase in excess lifetime associated with PAH exposure of First Nations’ people in the Cold Lake region.
Keywords: soil ingestion; risk assessment; aboriginal; First Nations; Alberta oil sands; in-situ bitumen extraction; mass balance; Cold Lake; PAH; soil; HHRA